Health Care Consumption during Pregnancy in relation to Maternal Body Mass Index: A Swedish Population Based Observational Study - Elisabeth S. Lindholm; Daniel Altman; Margareta Norman; Marie Blomberg (Hindawi Limited, 2015)
Objective. To assess whether antenatal health care consumption is associated with maternal body mass index (BMI). Design. A register based observational study. Methods. The Swedish Medical Birth Register, the Maternal Health Care Register, and the Inpatient Register were used to determine antenatal health care consumption according to BMI categories for primiparous women with singleton pregnancies, from 2006 to 2008, n=71,638. Pairwise comparisons among BMI groups are obtained post hoc by Tukey HSD test. Result. Obese women were more often admitted for in-patient care (p<0.001), had longer antenatal hospital stays (p<0.001), and were more often sick-listed by an obstetrician (p<0.001) during their pregnancy, compared to women with normal weight women. Preeclampsia was more than four times as common, hypertension five times as common, and gestational diabetes 11 times as common when comparing in-patient care, obese to normal weight women (p<0.001 for all comparisons). Underweight mothers had longer stay in hospitals (p<0.05) and hydronephrosis and hyperemesis gravidarum were more than twice as common (both p<0.001). Conclusion. Obese and underweight mothers consumed significantly more health care resources and obese women were significantly more often sick-listed during their pregnancy when compared to pregnant women of normal weight.